Clinical Pharmacology of Vinpocetine: Properties Revisited and Introduction of a Population Pharmacokinetic Model for Its Metabolite, Apovincaminic Acid (AVA) - Zvonimir Petric; Paulo Paixão; Augusto Filipe; José Guimarães Morais (MDPI AG, 2023)
This paper examines the use of vinpocetine in the context of clinical pharmacology. The main and active metabolite of vinpocetine is apovincaminic acid (AVA). Due to the scarce information in the literature on AVA pharmacokinetics, we propose a population pharmacokinetic (PopPK) model for AVA based on a study in healthy volunteers with three different formulations of vinpocetine. The suggested PopPK model (and simulations) could be helpful in ensuring the more effective and safer use of the vinpocetine in the future given the increasing range of suggested indications for its use.